Comparison of Carcass and Sensory Traits and Free Amino Acid Contents among Quality Grades in Loin and Rump of Korean Cattle Steer - Piao, Min Yu; Jo, Cheorun; Kim, Hyun Joo; Lee, Hyun Jung; Kim, Hyun Jin; Ko, Jong-Youl; Baik, Myunggi (Animal bioscience, 2015)
This study was performed to compare carcass traits, sensory characteristics, physiochemical composition, and contents of nucleotides, collagen, and free amino acids among quality grades (QG) and to understand the association between QG and above parameters in loin and rump of Korean cattle steer. Loin and rump samples were obtained from 48 Korean cattle steers with each of four QG (QG 1++, 1+, 1, and 2; average 32 months of age). Carcass weight and marbling score (MS) were highest in QG 1++, whereas texture score measured by a meat grader was highest in QG 2. A correlation analysis revealed that MS (r = 0.98; p<0.01) and fat content (r = 0.73; p<0.01) had strong positive correlations with QG and that texture had a strong negative correlation (r = -0.78) with QG. Fat content in loin was highest but protein and moisture contents were lowest in QG 1++. Our results confirmed that a major determinant of QG is the MS; thus, intramuscular fat content. The International Commission on Illumination L*, a*, and b* values in loin were highest in QG 1++. Numeric values of shear force in loin were lowest in QG 1++, whereas those of tenderness, juiciness, and overall acceptability tended to be highest in QG 1++ without statistical significance. QG was strongly correlated with juiciness (r = 0.81; p<0.01) and overall acceptability (r = 0.87; p<0.001). All sensory characteristics were higher (p<0.05) in loin than those in rump. Adenosine-5'-monophosphate (AMP) and inosine-5'-monophosphate (IMP) contents in both loin and rump did not differ among QGs. No nucleotide (AMP, IMP, inosine, hypoxanthine) was correlated with any of the sensory traits. Total, soluble, and insoluble collagen contents in loin were higher in QG 1++ than those in QG 1. All three collagens had lower content in loin than that in rump. All three collagens were positively correlated with tenderness, juiciness, and overall acceptability. Glutamic acid content did not significantly differ among the four QGs in either loin or rump. In conclusion, it is confirmed that QG is associated with sensory traits but nucleotide contents in beef may not be a major factor determining meat palatability in the present study.